Studies on SiO 2 -hybrid polymeric nanocomposite coatings with superior corrosion protection and hydrophobicity - Ammar, Sh.; Ramesh, K.; Ma, I.A.W.; Farah, Z.; Vengadaesvaran, B.; Ramesh, S.; Arof, Abdul Kariem (Elsevier, 2017)
Hybrid polymeric based nanocomposite coating systems (NCs) were fabricated by solution intercalation method with the use of epoxy (E) and polydimethylsiloxane (PDMS) as the host hybrid polymeric matrix and different weight ratio of SiO2 nanoparticles, ranging from 2 wt. % to 8 wt. %, as the reinforcing agents. The effects of introducing PDMS as a modifier to epoxy resin, as well as, the influence of embedding SiO2 nanoparticles within the developed matrix were evaluated via utilizing X-ray diffraction (XRD), contact angle measurements (CA), field emission scanning electron microscope (FESEM), and electrochemical impedance spectroscopy (EIS). XRD and FESEM results revealed the good dispersion of the nanoparticles within the polymeric matrix and confirmed the efficiency of the solution intercalation method. CA findings confirmed the achievement of hydrophobic surface after modifying epoxy resin with PDMS with CA value at 96° for epoxy-PDMS coating system (ES 0). Also CA results indicated the ability of SiO2 nanoparticles to participate in developing more hydrophobic surface as CA value up to 132° was achieved with utilizing 6 wt% SiO2 loading ratio. The results obtained from EIS studies revealed that the coating system with 2 wt% had the best anticorrosion performance and have demonstrated an intact behavior over all the immersion period without any sign of coating damage or degradation.